Effectiveness of Implementing Restorative Justice in Resolution of Child Crimes - Agung Setya Nugraha; Mahmutarom Mahmutarom; Adityo Putro Prakoso (UNISSULA, 2025)
This study examines the effectiveness of implementing restorative justice in resolving juvenile criminal cases in Indonesia. Restorative justice, as regulated in Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, emphasizes the principle of “the best interest of the child” by prioritizing diversion to avoid imprisonment. Using a normative juridical approach supported by empirical secondary data from KPAI, the Ministry of Law and Human Rights, and DPR RI, this research analyzes the gap between legal norms and field implementation. Findings show that although the legal framework strongly supports restorative justice, its application remains limited. In 2023, KPAI recorded 7,185 children under the supervision of correctional counselors, but only 2,296 cases were resolved through diversion, indicating suboptimal implementation. The effectiveness of restorative justice is hindered by limited understanding among law enforcers, insufficient institutional infrastructure, and a cultural paradigm that still prioritizes retributive justice. However, the existence of strong regulations, institutional support, and increasing public awareness serve as important supporting factors. The study concludes that restorative justice has significant potential as a humane and child-centered approach, but requires strengthening institutional capacity, enhancing inter-agency coordination, and shifting legal culture to achieve optimal implementation.